1978
DOI: 10.1038/273345a0
|View full text |Cite
|
Sign up to set email alerts
|

Role of cell shape in growth control

Abstract: Tissue culture plastic adhesivity was precisely varied by applying different concentrations of poly(2-hydroxyethyl methacrylate). The extent of cell spreading was thus accurately controlled so that cells cultured on these substrata could be held at any one of a graded series of quantitated cell shapes. Cell shape was found to be tightly coupled to DNA synthesis and growth in nontransformed cells. These findings suggest a mechanism that is important in growth control of mammalian cells, and provide a more funda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

60
1,148
3
2

Year Published

1980
1980
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 2,291 publications
(1,222 citation statements)
references
References 16 publications
60
1,148
3
2
Order By: Relevance
“…Thereafter, we examined the involvement of XEDAR in detachment-induced apoptosis. Fortyeight hours after transfection with plasmid expressing XEDAR, HEK293 cells were detached and cultured in suspension for 24 h using a poly-2-hydroxyethyl methacrylate-coated plate (Folkman and Moscona, 1978). Subsequent analyses indicated that XEDAR introduction reduced the number of viable cells through caspase-3 activation (Figure 3d).…”
Section: Role Of Xedar In Anoikismentioning
confidence: 99%
“…Thereafter, we examined the involvement of XEDAR in detachment-induced apoptosis. Fortyeight hours after transfection with plasmid expressing XEDAR, HEK293 cells were detached and cultured in suspension for 24 h using a poly-2-hydroxyethyl methacrylate-coated plate (Folkman and Moscona, 1978). Subsequent analyses indicated that XEDAR introduction reduced the number of viable cells through caspase-3 activation (Figure 3d).…”
Section: Role Of Xedar In Anoikismentioning
confidence: 99%
“…29 Addition of growth factors.Growth factors were added at a concentration of 10 ng/ml to AG 1518 fibroblasts cultured on poly[HEMA]-coated microtiter plates as described above. The growth factors were added after an initial incubation period of 2.5 hr and present during the entire [ 14 C]Glycine pulse period.…”
Section: Cell Culture Protocolsmentioning
confidence: 99%
“…These considerations suggest that CAM vascular growth may be initiated by a global trigger, but is placed under local control for down-regulation of endothelial cell proliferation in response to the hemodynamic and geometric constraints. It appears reasonable that intussusceptive mesh formation is the optimum way to realize this task of growth control via cell shape (compare Folkman and Moscona, 1978). This study is aimed at extending the concept of Patan et al (19931, by relating capillary endothelial cell proliferation to precapillary vessel formation.…”
Section: Introductionmentioning
confidence: 95%